Hot Rod Hamster meets his match! - Lord, Cynthia; Anderson, Derek, 1969-; Paprocki, Greg (New York : Scholastic Press, 2016)
When Hamster and his friends go looking for some cool, wet, wild fun at the Water Kingdom waterpark, Hamster and his new friend, Holly, challenge two dogs to a race down the waterslide. Can they win?
2.
K-2nd.
210
Keywords: Amusement parks -- Juvenile fiction; Dogs -- Juvenile fiction; Hamsters -- Juvenile fiction; Mice -- Juvenile fiction